1995
DOI: 10.1055/s-2007-979928
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation between Levels of Osteocalcin and Bone Alkaline Phosphatase in Healthy Control and Postmenopausal Osteoporotic Women

Abstract: The determination of bone alkaline phosphatase (bAR) by IRMA and the measure of intact osteocalcin (BGP) andlor different fragments by IRMA and/or RIA are new commercially available methods for the evaluation of osteoblast activity. The aim of this work was to study the possible correlation among serum bAR and levels of BGP measured by two different methods: an IRMA which only detects intact-BGP and a RIA which detects intact-BGP and carboxyterminal fragments (C-terminal BGP) in healthy postmenopausal control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…970) between bAP (Tandem-R Ostase IRMA) and tAP in Paget's disease, where the values of bAP varied widely. High or moderate correlations between bAP measured by IRMA or wheat germ agglutinin (WGA) have been reported in post-menopausal women (Diego et al, 1995;Bouman et al, 1995). In this study, because the correlation coefficient was high even in the healthy subjects in whom the data were less variable, the variations of the data did not greatly affect the correlation between tAP and bAP.…”
Section: Discussionmentioning
confidence: 65%
“…970) between bAP (Tandem-R Ostase IRMA) and tAP in Paget's disease, where the values of bAP varied widely. High or moderate correlations between bAP measured by IRMA or wheat germ agglutinin (WGA) have been reported in post-menopausal women (Diego et al, 1995;Bouman et al, 1995). In this study, because the correlation coefficient was high even in the healthy subjects in whom the data were less variable, the variations of the data did not greatly affect the correlation between tAP and bAP.…”
Section: Discussionmentioning
confidence: 65%
“…Significant associations between ALP and bone mineral density, after controlling for other variables, suggested that ALP might interacts with other factors, leading to alteration of bone metabolism 63 . In contrast, no relationship was found between ALP and bone density in elderly men, suggesting that ALP was not useful for monitoring bone integrity 64 , while no correlations were found between levels of osteocalcin and bone alkaline phosphatase in healthy and postmenopausal osteoporotic women 65 . The results of the present study showed that plasma ALP levels were elevated in PCOS-induced animals.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies indicated a higher level of tOC in PMO cases [ 113 121 ]. However, there are also researches reporting the same or even lower tOC level in osteoporotic patients [ 122 – 125 ]. Biver et al [ 126 ] and Liu et al [ 127 ] performed meta-analyses to compare several markers of bone turnover and found no significant difference in tOC level between osteoporotic and healthy individuals.…”
Section: Osteocalcin and Osteoporosismentioning
confidence: 99%